Tinjauan Yuridis Proses Penyelesaian SengketaWanprestasi Yang Dilakukan DebiturTerhadap Perjanjian Utang Piutang(Studi Kasus Di Pengadilan Negeri Surakarta) - Budiyanto, Arif; , Darsono, S.H.,M.H (2016)
The objectives of this research are to observe the settlement process of breach of contract conflict in court which was done by the debtors, to observe the judges' consideration in deciding the verdict for breach of contract conflict, to examine the juristic consequences for the debtors who violate the breach of contract in Loan Agreement. This research is a descriptive research which applies normative approach. The method used by the researcher to analyze the data is qualitative approach. The process and mechanism of the breach of contract conflict settlement involves several stages and procedures. First stage is the preparation: two or more parties involved in the conflict, the establishment of the lawsuit, the execution of the lawsuit, and court fee. Second stage is submission stage and lawsuit signing. Third stage is trial stage, involves: case and investigation on all partires involved, lawsuit lectetion, mediation, defendant answer, defendant plea, plaintiff hisrebuttal, verification, conclusion, verdict. The juristic consequence of the breach contract violation is mention in Civil Law Criminal Code, specifically in the thrid book related to verbintenis Chapter I. As mentioned in article 1236 Civil Law Criminal Code; "Those who owe must give refund fee, loss, and interest to the cessie if he or she is in the condition of not capable to turn in all of their possesion".